ISSUES OF TEACHING FOREIGN LANGUAGES TO THE STUDENTS OF FINE ARTS - Khayitmuradova, Shoira (Educational Research in Universal Sciences, 2023)
This article highlights the distinctive challenges and considerations associated with teaching foreign languages to students in the field of fine arts. The abstractdiscusses issues such as relevance, multimodal learning styles, time constraints, interdisciplinary collaboration, cultural sensitivity, portfolio enhancement, authentic language use, and motivation. By identifying these challenges and proposing thoughtful considerations, the abstractaims to guide educators in tailoring language instruction to meet the specific needs of fine arts students.